A systematic review of evidence for end-of-life communication interventions: Who do they target, how are they structured and do they work?. Issue 1 (January 2016) - Walczak, Adam; Butow, Phyllis N.; Bu, Stella; Clayton, Josephine M
Highlights: We synthesise evidence for interventions targeting end-of-life communication. Studies targeted patients, carers, health professionals or multiple stakeholders. Interventions had variable learning/behavior targets, structure, content and length Study designs, outcomes, settings, measures and quality were diverse. Most evidence is derived from less robust studies, more robust RCTs are needed. Abstract: Objective: To identify and synthesise evidence for interventions targeting end-of-life communication. Methods: Database, reference list and author searches were conducted to identify evaluations of end-of-life communication-focussed interventions. Data were extracted, synthesised and QUALSYST quality analyses were performed. Results: Forty-five studies met inclusion criteria. Interventions targeted patients ( n  = 6), caregivers ( n  = 3), healthcare professionals (HCPs n  = 24) and multiple stakeholders ( n  = 12). Interventions took various forms including communication skills training, education, advance care planning and structured practice changes. Substantial heterogeneity in study designs, outcomes, settings and measures was apparent and study quality was variable. Conclusion: A substantial number of end-of-life communication interventions have been evaluated. Interventions have particularly targeted HCPs in cancer settings, though patient, caregiver and multi-focal interventions have also been evaluated. While some interventions were efficacious in well-designed RCTs, most evidence was from less robust studies. While additional interventions targeting patients and caregivers are needed, multi-focal interventions may more effectively remove barriers to end-of-life communication. Practice Implications: Despite the limitations evident in the existing literature, healthcare professionals may still derive useful insights into effective approaches to end-of-life communication if appropriate caution is exercised. However, additional RCTs, implementation studies and cost-benefit analyses are required to bolster arguments for implementing and resourcing communication interventions.